Betterment capture for social redistribution: A developer obligation for touristic developments. (July 2022) - Rebelo, Emília Malcata
Graphical abstract: Highlights: Contribution to the debate towards international comparative research on developer obligations. Development of an innovative concept and methodology for value capture and its application. Endowment of Municipalities with financing efficient instruments to cover municipal costs and social goals. Proposal and explanation of a methodology to compute betterments engendered by territorial plans. Provision of technical studies as a prerequisite for the approval of territorial plans. Abstract: This article presents the results of a research project on the design of a particular value capture instrument in the form of a development obligation. This has been modelled to capture part of the betterment engendered by tourism-oriented plans. The article subsequently explores the potential of applying this levy in the interest of social goals, thus complementing traditional municipal funding sources. The concept is applied to the Urban Zoning Plan of the Planning Unit 11 of the municipality of Lagoa, located in the Algarve, Portugal. It tries to overcome several gaps and contradictions identified in the literature and in the planning practices of different value capture instruments in diversified urban contexts. These shortcomings refer to: (i) uncertainties as to why the land value rises; (ii) undefined thresholds between betterment and profit; (iii) the classification of value capture whether as a tax or as an instrument of wealth redistribution; (iv) the application of the captured value; (v) dilemmas between private property rights and citizens' rights over betterments due to public decisions; (vi) public regulation versus free market operation; (vii) responsibilities, benefits and obligations of private individuals in urban development; and (viii) the design, execution as well as the risks of capture instruments. This adds to the specific requirements enforced by the Portuguese Land Act regarding the economic and financial sustainability of urban development. This instrument is based on objective, reliable, and comparable data. This data is organised into a management information system which supports a flexible and continually updatable model to assess betterments engendered by public decisions. This model is easily generalizable to other urban contexts. Finally, the potential of the proposed instrument to achieve social goals is assessed against the background of factors such as the fiscal challenges currently faced by municipalities, the rising importance of increasingly diversified stakeholders and their awareness of issues of sustainability in urban development.